Meningkatkan Kemampuan Berhitung Melalui Pemamfaatan Media Balok Cusenaire Pada Kelompok A Tk.Dharma Wanita Setda Kota Surabaya - WIDYANINGSIH, RITA TATIK; Muzaqi, Sugto (MOTORIC, 2025)
ABSTRACT Tatik W, Rita. 2022. Meningkatan Kemampuan Berhitung Melalui Pemanfaatan Media Balok Cuisenaire Pada Kelompok A TK Dharma Wanita Setda Kota Surabaya. This research is motivated by building children's numeracy skills Kindergarten in understanding the concept of numbers by using Cuisenaire blocks as media. This study aims to improve numeracy skills through the use of Cuisenaire block media in Group A of Dharma Wanita Kindergarten Regional Secretariat of Surabaya City The subjects of this study were group A students, Dharma Wanita Kindergarten Regional Secretariat of Surabaya City, which consisted of 23 students. Learning to count in kindergarten still uses drill and practice methods practice the pencil paper test, this makes children feel bored and tired quickly. So that children's numeracy skills can develop better then it is necessary a fun medium that is with Cuisenaire beam media. This classroom action research was carried out through 2 cycles each each cycle has stages: planning, observation, evaluation, and reflection. Data collection techniques are tests and non-tes, non-test through observation, and tests through performance. Qualitative data analysis techniques and quantitative.This research is motivated by building children's numeracy skills Kindergarten in understanding the concept of numbers by using Cuisenaire blocks as media. This study aims to improve numeracy skills through the use of Cuisenaire block media in Group A of Dharma Wanita Kindergarten Regional Secretariat of Surabaya City The results showed that there was an increase in ability count with Cuisenaire beam media in each cycle. On the aspect understanding of numbers the initial condition of the child's ability is 40% which is developing very good, in the first cycle the child's ability increased to 66% and increased even better in cycle II, namely 86%. Aspect comparison, on initial conditions 37% which developed very well. And in cycle I increased 66%, and in cycle II it increased again to 86%. Aspect analysis and the probability in the initial condition of the child is 33%, while in cycle I it increases to 60%, and increased even better in cycle II, namely 86%. This increase exceeds the success indicator to be achieved, namely 80%. Based on this description, it can be concluded that by using Cuisenaire block media can improve the numeracy skills of kindergarten students group A. It is suggested that the teacher can develop more Cuisenaire block media varied to improve the numeracy skills of kindergarten children.